Efficacy of sushi rice acidification: Quantification of Bacillus cereus and Clostridium perfringens during simulation of retail practices. (September 2020) - Mohammad, Zahra H.; Payton, Larry; Sirsat, Sujata A.
Abstract: This study aimed to investigate the efficacy of sushi rice acidification on the growth of B. cereus and C. prefringens . The white sushi rice was cooked in a rice cooker, and the pH was adjusted with rice vinegar to 4.2 ± 0.05 or 4.6 ± 0.05 to compare pH recommended by the U.S. Food Code and lower pH used by sushi retails. The rice was inoculated with C. perfringens, and B. cereus to a final count of 10 4  CFU/g and was held at room-temperature (23 ± 1) or 37.7 ± 1 °C. Three samples were taken at time zero, 12, and 24 h post-inoculation and plated on selective media for pathogens quantification. The means and S.D. of B. cereus and C. perfringens at time zero were 3.4 ± 0.2 and 3.0 ± 0.2 log CFU/g respectively. No recovery of C. perfringens and B. cereus was found at time 12 or 24 h when held at room-temperature at pH 4.2 ± 0.05, while B. cereus were survived pH 4.6 ± 0.05 at both storage times. However, both pathogens were significantly recovered when held at 37.7 ± 1 °C at pH 4.2 ± 0.05 and 4.6 ± 0.05. These results demonstrate that acidified white rice with a pH 4.2 inhibits the growth C. perfringens and B. cereus at room-temperature for up to 24 h. Highlights: Improper sushi rice acidification at sushi retail could enhance pathogens growth. B. cereus & C. prefringens may survive sushi rice if not acidified or stored adequately. B. cereus & C. prefringens were recovered when rice held at 37.7 ± 1 °C with pH 4.2 or 4.6. Proper rice acidification with a pH of 4.2 stored at room temperature inhibits pathogen growth.